\(\left(x+1\right)^2+\left(y+1\right)^2+\left(x-y\right)^2=2\Rightarrow\left(x+1\right)^2\le2\Rightarrow\orbr{\begin{cases}\left(x+1\right)^2=0\\\left(x+1\right)^2=1\end{cases}}\)
- \(\left(x+1\right)^2=0\Leftrightarrow x=-1\).
Với \(x=-1\): \(\left(y+1\right)^2+\left(y+1\right)^2=2\Leftrightarrow\orbr{\begin{cases}y=-2\\y=0\end{cases}}\).
- \(\left(x+1\right)^2=1\Leftrightarrow\orbr{\begin{cases}x=0\\x=-2\end{cases}}\).
Với \(x=0\): \(1+\left(y+1\right)^2+y^2=2\Leftrightarrow2y^2+2y=0\Leftrightarrow\orbr{\begin{cases}y=0\\y=-1\end{cases}}\).
Với \(x=-2\): \(1+\left(y+1\right)^2+\left(y+2\right)^2=2\Leftrightarrow2y^2+6y+4=0\Leftrightarrow\orbr{\begin{cases}y=-1\\y=-2\end{cases}}\).
Vậy \(\left(x,y\right)\in\left\{\left(0,0\right),\left(0,-1\right),\left(-2,-1\right),\left(-2,-2\right),\left(-1,-2\right),\left(-1,0\right)\right\}\).